Evaluation of "Live for Life", a health promotion programme in the County of Skaraborg, Sweden. Issue 4 (1st April 2001) - Lingfors, H; Lindström, K; Persson, L-G; Bengtsson, C; Lissner, L
Abstract : STUDY OBJECTIVE: To evaluate a health promotion programme, combining a population and individual based strategy, in the County of Skaraborg, Sweden, with special attention to outcome. DESIGN: The evaluation was subdivided into structure, process and outcome. The evaluation procedure as a total is described here, but the results presented refer only to outcome. In order to study the potential effect of the individually based health examination, 35 year old subjects who had participated five years previously were in 1994–1996 compared with 35 year old subjects who had not participated before, and compared with their own values five years earlier. The results during 1995–1996 were compared with those of 1989–1990 for corresponding ages in order to study the effect of, particularly, the population based strategy. SETTING: The County of Skaraborg in the south western part of Sweden with about 270 000 inhabitants. In addition to population strategy, involving the total county, men and women aged 30 and 35 years were invited to an individually based examination. MAIN RESULTS: Factors related to body weight increased during the study period, while other factors mostly changed in the direction wanted. As a whole the changes were rather modest. There were favourable changes in lifestyle variables, for example, concerning smoking and dietary habits. CONCLUSIONS: There were beneficial effects from the health promotion programme, but there is a need for continuous improvement of methods of intervention referred to lifestyle.